Analisis Stabilitas Model SIR (Susceptibles, Infected, Recovered) Pada Penyebaran Penyakit Demam Berdarah Dengue di Provinsi Maluku - Leleury, Zeth Arthur; Lesnussa, Yopi Andry; Bension, Johan Bruiyf; Kakisina, Yulia S. (Jurnal Matematika; Vol 7 No 2 (2017), 2018)
Health is an investment to support economic development and has an important role in efforts to reduce poverty and improve the quality of human resources. One of the diseases that often become serious problem in health sector that is Dengue Hemorrhagic Fever (DHF). In Indonesia, many mosquitoes cause dangerous DHF such as Aedes aegypti, Aedes albopictus, Aedes africanus, anopheles and others. In this study, we analyzed and applied SIR (Susceptible, Infection, Recovered) mathematical models and their interpolation to determine whether a contagious disease (DHF) can become endemic or not. Therefore, in this study aimed to determine the a special form of model of SIR to analyze the spread of DHF in Maluku Province and the stability analysis of this model and also interpolating the data of DHF transmission in Maluku Province. Furthermore, it can be obtained the characteristics of equilibrium point of each sub population. Based on the research conducted it can be concluded that from the entire population of Maluku Province is 1.686.469 vulnerable people infected with DHF and endemic disease with the basic reproduction value is 3,44.